Accessory Muscles of the Extremities - Vanhoenacker, Filip M.; Desimpel, Julie; Mespreuve, Marc; Tagliafico, Alberto (Seminars in Musculoskeletal Radiology, 2018)
Accessory muscles and variations are not uncommon at the upper and lower extremity. They are often overlooked because they are asymptomatic and present as incidental findings on imaging. However, they may present as a soft tissue swelling, thereby mimicking soft tissue tumors. Other symptoms are attributed to impingement on neurovascular structures and to exercise-related pain. Thorough knowledge of the anatomy, systematic imaging analysis, and the awareness of it are the clues to correct identification. On ultrasound, accessory muscles have a similar echotexture as other muscles, whereas the signal intensity on magnetic resonance imaging (MRI) is similar to muscle. Because of the intrinsic contrast with the adjacent intermuscular fat, accessory muscles are best depicted on MRI without fat suppression. This article provides a short overview of the anatomy of most prevalent accessory muscles of the upper and lower limb and its potential pathogenic nature.
Keywords: accessory muscle; variants; ultrasonography; magnetic resonance imaging